Caleidoscopio ischitano - Clerici, Luca; Grazioli, Elena (Kritik. Rivista di letteratura e critica culturale, 2024)
In the wake of the volume Dadapolis. Caleidoscopio napoletano, by Fabrizia Ramondino and Andreas Friedrich Müller, this contribution accepts the invitation by pointing the ‘magic tube’ at Ischia, and changing the rules of the game a little. The testimonies collected here are exclusively by Italian travellers, and only from the eighteenth century to the present day, i.e. from the time when the civilisation of modern travel was born with the Grand Tour. This is a considerable limitation of the field of enquiry, which nevertheless remains very broad: from the Age of Enlightenment onwards, the accounts of those who visited the island are innumerable. An ample registry is proposed here following a thematic but not temporal order, because what guides us in the choice of topics is a travel account by an Italian in Italy, chosen as Baedeker, Carlo Bernari’s Taccuino Ischitano. The aim of the research is to create an evocative ‘Ischian kaleidoscope’, collecting testimonies by frequenters – whether regular or not – of the island, such as Spallanzani, Stoppani, Piovene, Comisso, Regaldi, Barilli, Gamba, Monnelli, Pasolini...